VPS45 is required for both diffuse and tip growth of Arabidopsis thaliana cells - Mugume, Yosia; Roy, Rahul; Agbemafle, William; Shepard, Gabriella N.; Vue, Yee; Bassham, Diane C. (Frontiers in Plant Science, 2023)
VPS45 belongs to the Sec1/Munc18 family of proteins, which interact with and regulate Qa-SNARE function during membrane fusion. We have shown previously that Arabidopsis thaliana VPS45 interacts with the SYP61/SYP41/VTI12 SNARE complex, which locates on the trans-Golgi network (TGN). It is required for SYP41 stability, and it functions in cargo trafficking to the vacuole and in cell expansion. It is also required for correct auxin distribution during gravitropism and lateral root growth. As vps45 knockout mutation is lethal in Arabidopsis, we identified a mutant, vps45-3, with a point mutation in the VPS45 gene causing a serine 284-to-phenylalanine substitution. The VPS45-3 protein is stable and maintains interaction with SYP61 and SYP41. However, vps45-3 plants display severe growth defects with significantly reduced organ and cell size, similar to vps45 RNAi transgenic lines that have reduced VPS45 protein levels. Root hair and pollen tube elongation, both processes of tip growth, are highly compromised in vps45-3. Mutant root hairs are shorter and thicker than those of wild-type plants, and are wavy. These root hairs have vacuolar defects, containing many small vacuoles, compared with WT root hairs with a single large vacuole occupying much of the cell volume. Pollen tubes were also significantly shorter in vps45-3 compared to WT. We thus show that VPS45 is essential for proper tip growth and propose that the observed vacuolar defects lead to loss of the turgor pressure needed for tip growth.